Potensi Pseudomonas sp. Dalam Bioremediasi Limbah B3 Merkuri Berdasarkan Tinjauan Literatur - Laksono, Tomi (Maliki Interdisciplinary Journal, 2026)
Hazardous waste containing mercury is one of the dangerous environmental pollutants due to its toxic, persistent nature and ability to accumulate in the food chain. Conventional mercury waste treatment efforts often require high costs and potentially cause secondary environmental impacts. Therefore, bioremediation using microorganisms has become a more environmentally friendly alternative. This research aims to examine the potential of Pseudomonas sp. in the bioremediation process of mercury hazardous waste based on a literature review. The method used is a literature study by analyzing relevant national and international scientific articles from the past ten years. The review results show that Pseudomonas sp. has good adaptive capabilities in mercury-contaminated environments and is able to reduce mercury concentrations through various mechanisms, such as biosorption, bioaccumulation, and enzymatic transformation. Based on these review findings, Pseudomonas sp. has great potential to be developed as a sustainable and environmentally safe bioremediation agent for mercury hazardous waste.